Late Postpartum Eclampsia with Posterior Reversible Encephalopathy Syndrome and Subarachnoid Hemorrhage: A Case Study - Mohamed Elshafei; Hala Ashraf Oweis; Yosra Abdul Hafez; Thuraya Alom; Zahraa Mohamed Hayani; Eslam ElNebrisi (Medicina)
Eclampsia is a multisystem disorder of pregnancy and the puerperium. Posterior reversible encephalopathy syndrome (PRES), a neurotoxic condition characterized by various neurological symptoms, can arise from multiple causes including eclampsia. Although hemorrhage is a possible complication of PRES, subarachnoid hemorrhage (SAH) is a rare occurrence in eclamptic patients with this condition. A 33-year-old female patient presented with acute severe headache and blurred vision two days after delivery. This progressively worsened over the next five days before she was admitted to the hospital. A magnetic resonance imaging (MRI) brain scan with contrast revealed a picture suggestive of PRES. Following admission, she had seizures, and a follow-up MRI revealed an acute subarachnoid hemorrhage. Treatment started, and the patient improved and was discharged from the hospital without any residual symptoms. This case illustrates how eclampsia can be a risk factor for PRES, and although hemorrhagic PRES is becoming more recognized, SAH remains an unusual but critical presentation. Early and accurate diagnosis, along with effective management, is crucial for achieving a positive outcome.